BASLAWÍSH KLASS OQÍWSHÍLARÍN KITAP OQÍWǴA QÍZÍQTÍRÍW BARÍSÍNDAǴÍ WAZÍYPALAR - Ilyasova, Z.U. (SCIENCE and SOCIETY, 2020)
The article deals with the issues of formation and development of reading skill of the pupils of primary classes. The author of the article gives some recommendations how to evoke an interest to independent reading and to snow the role of a book in our life.